2022
DOI: 10.1212/wnl.0000000000200609
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Seizure Recurrence on 1-Year Functional Outcome and Mortality in Patients With Poststroke Epilepsy

Abstract: Background and Objectives:The functional outcome and mortality of post-stroke epilepsy (PSE) patients have not been assessed in a prospective study. Previous reports have suggested that PSE patients may suffer from prolonged functional deterioration following a seizure. In the current study, we prospectively investigated the functional outcome and mortality of PSE patients and analyzed the impact of seizure recurrence on the outcomes.Methods:This is part of the Prognosis of Post-Stroke Epilepsy (PROPOSE) study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
0
14
1
Order By: Relevance
“…Post-stroke seizures are associated with a worse functional outcome, a higher mortality rate and increased risk of comorbidities [4]. Many risk factors of PSSs (cortical involvement, haemorrhagic transformation, intracerebral haemorrhage [5] and baseline stroke severity [6]) have been identified; however, the role of endovascular treatment (EVT) for PSSs is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Post-stroke seizures are associated with a worse functional outcome, a higher mortality rate and increased risk of comorbidities [4]. Many risk factors of PSSs (cortical involvement, haemorrhagic transformation, intracerebral haemorrhage [5] and baseline stroke severity [6]) have been identified; however, the role of endovascular treatment (EVT) for PSSs is controversial.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 Previous studies have demonstrated that the presence of PSE was associated with neurological worsening, 8 changing the modified Rankin scale (mRS) from 3 to 4, 9 and functional decline. 10 Another study reported that health-related quality of life score was reduced in patients with PSE, and seizure frequency was an independent determinant of health-related quality of life score in patients with PSE. 11 Furthermore, patients with PSE have a higher risk of short- and long-term mortality within 30-day and 20-year post seizures, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with PSE are more likely to have neurological sequelae due to stroke or aging‐related comorbidities than those with other focal epilepsies, 2 and additional postseizure functional decline may have a significant effect. Our recent study demonstrated that 11.8% of patients with PSE and first‐ever seizures had a long‐term functional decline 1 year after discharge 3 . However, data on electroencephalogram (EEG) markers associated with postseizure short‐term or long‐term functional decline in PSE are scarce.…”
Section: Introductionmentioning
confidence: 99%